Implementation of the Family Welfare Rice Program in an Effort to Improve the Welfare of the Poor - Jamaluddin; Anita Harman; Risma Niswaty; Suprianto (ASHA Publishing, 2024)
The prosperous family rice program is a food subsidy program (rice) for low-income people. The goals and targets of food subsidies (Rastra) are placed by the government in the national development agenda so that in the future development of rastra into nutritional food assistance. This study aims to determine the implementation of the Family Welfare Rice Program in an effort to improve the welfare of poor people in Lalabata Rilau Village, Lalabata District, Soppeng Regency.The type of research used is qualitative descriptive. In this study, the data collection techniques used were observation, interview, and documentation techniques. The data analysis techniques used are data collection, condensation, data presentation and conclusion. Informants are Lurah, Rastra Distributors, and the Community. The results of this study show that the implementation of the Family Welfare Rice Program in an effort to improve the welfare of the poor in Lalabata Rilau Village, Lalabata District, Soppeng Regency has been carried out quite well, but still needs improvement in supporting the implementation of the Rastra program. This data is seen from the results of research on each dimension, namely the standards and targets of Rastra distribution have met the criteria. My resources in distributing Rastra have been adequate. Relations between organizations from the center to the regions have collaborated well. The characteristics of the implementing agents of the Rastra team have been good but still need to be improved. The disposition of good implementors has been proven by the realized Rastra Program, and social, economic and political conditions have been good with support from various parties. This research can be used as information in providing an in-depth understanding of poverty alleviation, and the implementation of rastra distribution because it is different from previous studies.